Initial Results of the HELENA Survey Conducted in Estonia with Comparison to Results from Sweden and Worldwide - Scott, Ezequiel; Pfahl, Dietmar; Hebig, Regina; Heldal, Rogardt; Knauss, Eric (Product-Focused Software Process Improvement, 2017)
The way how software is developed in industry has considerably changed with the advent of the agile development paradigm about 20 years ago. The HELENA initiative tries to investigate the current state of practice in software and system development. This paper reports about initial results of an online survey that was conducted in 26 countries simultaneously, focusing on results from Estonia and comparing these results with results from Sweden as well as with the joint results from all participating countries worldwide.